Subjective Aspects of Economic Poverty - Ordered Response Model Approach - Dudek, Hanna (Analiza subiektywnych aspektów ubóstwa na podstawie podejścia wykorzystującego uporządkowane modele logitowe, 2009)
In the paper the subjective economic poverty in Polish households is analysed. The study is based on the Household Budget Survey carried out by the Central Statistical Office in Poland. Subjective measures are estimated using households’ answers to questions about the own satisfaction with their financial situation. The inspiration for this research comes from J. Schwarze’s article [17] where ordered logit model was applied to estimate the equivalence scale elasticity. Such a model implicitly assumes that the effects of the explanatory variables are identical at each cut-off point between categories, what is known as the „parallel regression assumption”. The paper indicates the violation of this assumption for the sample of Polish households of retirees as the whole, while the assumption cannot be rejected when we exclude the poorest and richest households. Some of the results described here are similar to typical findings in poverty research, such as U-shaped relationship between age and subjective income satisfaction. Different results are found with regard to gender of household head. Also, as compared with other research data for Poland, the method applied here produces higher equivalence scale elasticity.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 73, s. 9-24